Prevalensi Hiperurisemia pada Kelompok Lansia Segara Santhi di Desa Kelating, Kerambitan Tabanan: Studi Cross Sectional - Aryani, Ni Made; Fahira, Cindy; Lestari, I Dewa Ayu Made Dian; Putra, Kadek Nova Adi; Wirawan, I Made Suma (Syntax Literate, 2025)
This study examines the design of a collaboration between SMEs producing goat milk soap and the Hilton hotel chain, aiming to identify an effective and sustainable partnership model. Using a qualitative approach with a case study design, the research involves in-depth interviews, observations, document analysis, and focus group discussions with various stakeholders. The results reveal that successful partnerships require knowledge and technology transfer, production capacity enhancement, quality standardization, and joint marketing strategies. The findings indicate significant potential for improving SME competitiveness, diversifying hotel products, and promoting local economic development. However, challenges such as differences in operational scale, investment needs, and regulatory adaptation need to be addressed. The proposed partnership model emphasizes the importance of long-term commitment, human resource development, and integration of sustainable practices. This research contributes to the understanding of SME-large enterprise partnership dynamics and offers practical implications for policymakers and business practitioners.